Practitioner-Based Measurement: A Collaborative Approach. - PARKINSON, S. T.; HIERONS, R. M.; LYCETT, M.; NORMAN, M. (Communications of the ACM, 2010)
The article examines frameworks for measuring improvement in software quality. Methods discussed include the Goal Question Metric paradigm, the AMI approach, and the MQG method. Frameworks can be categorized as either top-down or bottom-up, and after noting the benefits and drawbacks to these categories the authors present their own hybrid approach that they term a Practitioner-Based Model (PBM). An implementation of PBM at an information -technology department of the AXA Group is described and evaluated.